An evaluation of Musyawarah Guru Mata Pelajaran (MGMP) program of Indonesian Language subject in vocational school - Sigit Pambudi; Istiana Hermawati (Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
This study aims to evaluate the administrative program for Indonesian MGMP teachers, one of which is the Rencana Pelaksanaan Pembelajaran (RPP). This research is evaluation research with the CIPP model. The research population was 59 members of the Indonesian Language MGMP of vocational school at the Sleman Regency Vocational and all students whom the members of the MGMP taught. The teacher sample was selected using the total sampling technique involving 59 members, while the student sample was selected using the proportionate random sampling technique involving 375 students. The validity in this study uses content validity and construct validity, while the reliability uses Cronbach's Alpha. Data were collected using questionnaires, interviews, and observations and were analyzed using descriptive statistics. The results of the study show that: (1) the context of the Indonesian MGMP teacher administration program includes: program design, uses, and barriers based on teacher perceptions, the category is good at 33; (2) inputs include: infrastructure, materials, and instructors. Based on the teacher's perception, the category is good at 56; (3) the process includes: material presentation, discussion and question and answer, and making lesson plans based on the teacher's perception, the category is good at 69; (4) products in the form of teacher-made lesson plans based on perceptions the teacher category is good at 48; and product in teacher teaching abilities based on student perceptions have a good category by 80.